2018
DOI: 10.1097/iop.0000000000001103
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Dry Eye Parameters After Müller’s Muscle-Conjunctival Resection

Abstract: MMCR does not appear to change clinically meaningful ocular surface disease parameters, and postoperative dryness did not result from this procedure. In appropriately selected patients, MMCR can be safely performed without increased concerns regarding postoperative dry eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Additionally, Dailey et al 26 determined that conjunctivo-mullerectomy did not affect tear production. Another study ascertained no changes in the ocular surface disease parameters of tear breakup time, lipid layer thickness, and osmolarity after this surgery 27 . Our results agree with these prior ndings in that we found punctate epithelial erosion in 40 eyes (15.5%) without signi cant symptoms or the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Dailey et al 26 determined that conjunctivo-mullerectomy did not affect tear production. Another study ascertained no changes in the ocular surface disease parameters of tear breakup time, lipid layer thickness, and osmolarity after this surgery 27 . Our results agree with these prior ndings in that we found punctate epithelial erosion in 40 eyes (15.5%) without signi cant symptoms or the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Dailey et al 28 determined that conjunctivo-mullerectomy did not affect tear production. Another study ascertained no changes in the ocular surface disease parameters of tear break-up time, lipid layer thickness, and osmolarity after this surgery 29 . Our results agree with these prior findings in that we found punctate epithelial erosion in 40 eyes (15.5%) without significant symptoms or the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The Fasanella-Servat procedure includes the addition of a superior tarsectomy with the typical Muller muscle conjunctival resection 38. Dry eye disease can be an unwanted side effect of a transconjunctival approach due to transection of the goblet cells and accessory lacrimal glands, but studies have shown that tear break up times in postoperative patients are similar following surgery 75,77. Corneal abrasions should also be closely monitored with the addition of a superior tarsectomy.…”
Section: Acquired Causesmentioning
confidence: 99%